2019
DOI: 10.1002/ijop.12603
|View full text |Cite
|
Sign up to set email alerts
|

Reducing drug and alcohol use and improving well‐being for Indigenous and non‐Indigenous Australians using the Community Reinforcement Approach: A feasibility and acceptability study

Abstract: There is a lack of evidence of effective and appropriate drug and alcohol treatment for Aboriginal and Torres Strait Islander peoples. This paper contributes to addressing the evidence gap by examining the feasibility and acceptability and conducting a pre/post‐evaluation of the Aboriginal‐adapted Community Reinforcement Approach (CRA) delivered in New South Wales, Australia. Aboriginal and non‐Aboriginal clients (n = 55) received tailored CRA delivery between March and November 2013. Compared to the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…A commentary describing the lessons learned from a suicide prevention program spanning a 14-year period was also included [ 16 ]. Aboriginal and Torres Strait Islander people were the intended target population in four of the suicide prevention initiatives [ 17 , 18 , 19 , 20 ]. One study [ 21 ] discussed how adult males in farming communities were the intended target population; however, it was decided to allow female participation to avoid potential harm from exclusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A commentary describing the lessons learned from a suicide prevention program spanning a 14-year period was also included [ 16 ]. Aboriginal and Torres Strait Islander people were the intended target population in four of the suicide prevention initiatives [ 17 , 18 , 19 , 20 ]. One study [ 21 ] discussed how adult males in farming communities were the intended target population; however, it was decided to allow female participation to avoid potential harm from exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Most suicide prevention initiatives took place in rural and regional New South Wales [ 16 , 17 , 18 , 24 , 25 ]. One initiative occurred in Echuca, Victoria [ 19 ], and the same initiative in Tasmania was evaluated twice [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exciting new areas of research and translation are adapting these approaches specifically for pregnancy, including Aboriginal-led development of approaches that incorporate the whole community to support women. Although there is currently little evidence of effectiveness of community-based approaches [32], emerging research demonstrates their feasibility and acceptability when adapted for Aboriginal communities [53,54]. Additionally, there is evidence that combinations of family, school, and community approaches can be effective in reducing alcohol consumption generally [32].…”
Section: Preventing Pae and Promoting Maternal And Child Healthmentioning
confidence: 99%
“…One CRA implementation with AI adults with severe AUD found improved AUD outcomes at the 6-month follow-up [36]. A small, single group, feasibility and acceptability study of culturally tailored CRA with Aboriginal and non-Aboriginal participants found significant reductions in substance use at the 3-month follow-up [37].…”
Section: Introductionmentioning
confidence: 99%